THE EFFECTIVENESS OF ONLINE BIOLOGY LEARNING DURING COVID-19 PANDEMIC AT MADRASAH ALIYAH NEGERI IN ACEH BESAR REGENCY - Hanim, Nafisah; Nauli Taib, Eva; Ahadi, Rizky (Jurnal Biologi Sains dan Kependidikan, 2022)
The learning media used today during the covid-19 pandemic of whatsapp, zoom, Google form and Google classroom by taking advantage of Internet networks in use. Observing the results of observations made at the MAN Aceh Besar school shows that there is no face-to-face learning process. The dominant learning media is being used is the whatsapp because it is easy to be used by teachers and students from other media, so teachers must submit materials using whatsapp in order for the learning process to continue properly. This study is intended to compare the effectiveness of online learning during the covid-19 pandemic of biology subjects in 3 schools MAN Aceh Besar. The population in this research is MAN 1, MAN 2 and MAN 4 Aceh Besar. The sample in this study is the four teachers of the XI class of biology class. Data collection techniques are employed by using an questionnaire to know the effectiveness of online learning during the covid-19 pandemic of biology subjects. Data of effectiveness is analyzed using a percentage formula. Research is known to study online during the covid-19 pandemic of biology at 3 MAN Aceh Besar schools of 72% at effective levels.